THE EFFECT OF DIGITAL LEADERSHIP PRACTICE AND LEARNING ORGANIZATION RELATIONSHIP ON INDIVIDUAL PERFORMANCE - VALIZADA, Umid (Annals of Spiru Haret University. Economic Series, 2022)
Human life is like swimming against the current. If a person is not making an effort to move forward, the current will undoubtedly drag him further back at any moment. This is true for every area touched by human hands. In business life, institutions have to swim against the current, just like people. Today, digital transformation and its effects emerge as a topic that is discussed extensively in academia and practice and constitutes the business agenda of companies. The digital age changes not only the way of doing business, but also customer relations, service models, product styles and most of all, the perception of "talent". This rapid transformation in business strategies has led to the emergence of digital leaders with new and different skills in the short term. These leaders focus on different points than traditional leaders. The aim of this study is to examine the effects of the digital age on leadership theory, how the new leadership model is defined and the studies carried out in the relevant period in order to reveal its dimensions.